Sampling Searching for Science – how we shifted from face-to-face to online workshops for postgraduate students during Covid-19 lockdown - Baxter K; Clarke U; Mu C; Cook S; Smith E; McKeagg S (My University)
This session is for librarians with an interest in team teaching, flipped classroom methods, and active learning in online workshops. Science Librarians at Massey University New Zealand have run monthly Searching for Science workshops to support PhD and Masters students working on literature reviews since 2015. When Covid-19 lockdowns commenced in March 2020 our team rapidly transitioned into working from home and commenced delivering these monthly workshops online using Zoom and Adobe Connect. In keeping with the student-centred/active learning pedagogy of the face to face workshops, we decided to continue with and adapt these activities in the online environment. We will share our experiences in working with postgraduate students to achieve learning outcomes: • Networking & engaging activities to support a research community • Analysing a topic • Creating an advanced search strategy • Selecting and using tools Attendees will experience and evaluate active learning techniques for online workshops.
Keywords: Information literacy; Research services; evidence based; pedagogy; student led / informed; contextualised; agile; team led collaboration